The Role of Siak District Library and Archives Office in Disaster Mitigation - Yazid Tantri Puspita; Salam Noor Efni; Iskandar Dahrial; Hardianti Fitri; Elsarena Mai Sela Rosa; Wahidar Tutut Ismi (E3S Web of Conferences)
Siak is one of the districts in Riau Province. Siak is one of the areas indicated to be hit by a number of serious natural disasters in the last four years, this is confirmed based on data released by the 2024-2028 Disaster Risk Assessment (KRB). Some disasters that are indicated to have a more frequent frequency level in Siak include floods, extreme weather, extreme heat waves, abrasion, forest and land fires, drought, disease outbreaks, earthquakes to landslides. Serious efforts are needed in reducing disaster risk (disaster mitigation) so that Siak Regency becomes a district that is conducive and emergency-responsive in the face of future disasters. One of the agencies that plays an important role in this disaster mitigation process is the Library and Archives Office of Siak Regency. The purpose of this research is to find out the disaster mitigation process carried out by the Library and Archives Office of Siak Regency. The method used is qualitative, with data collection techniques using in-depth interviews and observation. The data analysis technique used is Miles and Huberman, and the data validity technique uses triangulation. It is hoped that this research can produce a disaster mitigation model by the Library and Archives Office in Siak Regency.